Compost Preparation from Different Organic Wastes: Their Biochemical Analysis and Effect on Growth of Bottle Gourd - Taneja, Tanvi; Sharma, Indu; Kumar, Mukesh; Rana, Mahesh Kumar; Singh, Raj (Asian Journal of Biological and Life Sciences)
Aim: A study was carried out to prepare from the different organic wastes and to assess their effect on bottle gourds. Background: Composting is a crucial agricultural process that aids in the recycling of agricultural and farm wastes. Beneficial microbes and plant nutrients are abundant in high-quality compost. It is a natural process to break organic matter, like leaves and food scraps, into useful manure, which is then used as manure to enrich the soil with carbon and nitrogen, phosphorus, potassium and especially micronutrients, essential for the growth of the plants. Materials and Methods: Four types of compost were prepared from (i) leaves (ii) fruits and vegetables, waste (iii) cow dung 2 years old (iv) cow dung 4 years old which were analyzed for pH, electrical conductivity, moisture content, bulk density and ash content. These composts were also analyzed for nitrogen, phosphorus and potassium content. Results: Out of the four composts, the compost prepared from leaves had the maximum pH (7.69), electrical conductivity (8.44 S/m), moisture content (55%) and bulk density (0.57 g/cm3) as compared to the rest of the three composts. Compost prepared from fruits and vegetable wastes had the maximum concentration of nitrogen (1.5%), potassium (1.2%) and phosphorus (0.8%) as compared to compost prepared from leaves, vegetables and cow dung. The study also revealed the significantly positive effect of composts on vine length and number of leaves per plant of bottle gourd (Lagenaria siceraria) 10, 15, 30, 50 and 70 days after the application of composts. Conclusion: Composting recycles a variety of organic materials, which would otherwise be considered garbage. These processes play a significant role in sustainable agriculture and organic farming.
Keywords: Bottle gourd; Compost; Plant growth; Plant nutrients; Soil carbon